Fecal microbiota transplantation for treatment of refractory or recurrent Clostridioides difficile infection in Taiwan: a cost-effectiveness analysis - Lan, Kai-Yen; Le, Puo-Hsien; Chiu, Cheng-Tang; Chen, Chien-Chang; Yeh, Yuan-Ming; Cheng, Hao-Tsai; Kuo, Chia-Jung; Chen, Chyi-Liang; Chen, Yi-Ching; Yeh, Pai-Jui; Chiu, Cheng-Hsun; Chang, Chee-Jen (Frontiers in Medicine, 2023)
Background Compared to antibiotic treatment, fecal microbiota transplantation (FMT) is a more effective treatment for refractory or recurrent CDI (rCDI). Patients with inflammatory bowel disease (IBD) have a higher incidence of CDI and worse outcomes. There has been no study from Asia to evaluate the cost-effectiveness of FMT for overall rCDI patients and rCDI patients with IBD. Methods We applied a Markov model with deterministic and probabilistic sensitivity analyses to evaluate the cost and effectiveness of different treatments for rCDI patients with a time horizon of 1 year from the payer's perspective. We compared the cost and clinical outcomes of FMT through colonoscopy to two antibiotics (vancomycin and fidaxomicin) using data from Chang Gung Memorial Hospital, Taoyuan, Taiwan. Results Compared to vancomycin, FMT was cost-effective in overall rCDI patients as well as IBD patients with rCDI [USD 39356 (NT$1,101,971.98)/quality-adjusted life year (QALY) gained in overall patients; USD65490 (NT$1,833,719.14)/QALY gained in IBD patients]. Compared to fidaxomicin, FMT was only cost-effective in overall rCDI patients [USD20255 (NT$567,133.45)/QALY gained] but slightly increased QALY (0.0018 QALY gained) in IBD patients with rCDI. Conclusion FMT is cost-effective, compared to vancomycin or fidaxomicin, for the treatment of rCDI in most scenarios from the payers' perspective in Taiwan.